“as Mulheres Não São uma Ferramenta para Os Homens”: (re)formulação e Revozeamento em um Debate em Sala de Aula - Goulart, Ana Carolina Fracalossi (2020)
This thesis aims to describe and analyze the use ofreformulation and revoicing in the realization of an activity such as a "class debate" in the context of talk-in-interaction in a classroom of a public elementary school in a municipality in the Greater V